Si it is a linear eqaution
X=-1 and y=3
To solve this, because y is equal to 2x+5, you can substitute 2x+5 into the bottom equation for y.
You now have 3x - (2x + 5) =-6
This can be solved like a normal equation. Multiply each term in the parenthesis by -1.
3x - 2x - 5 = -6
Subtract 2x from 3x
x - 5 = -6
Add 5 to both sides
x=-1
Now you can solve for y by plugging -1 in for x in either equation. Im going to use the top one.
y= 2(-1)+5
y= -2+5
y=3
You can check your answer by plugging in the values for x and y into both equations and making sure both sides equal each other.
Answer:
12.99km
Step-by-step explanation:
Using the formula
C=2(pi)(r)
A good way to think of it is in US quarters, 4 go into a dollar which is a whole or 100. Each quarter is 25 cents. Each quarter of a circle is 25%, so it would be 75%
Answer:
3x-9 is the answer on edgenuity:)
Step-by-step explanation: